An exploratory study of student, speech–language pathologist and emergency worker impressions of speakers with dysarthria. (4th May 2021) - Connaghan, Kathryn P.; Wertheim, Chelsea; Laures-Gore, Jacqueline S.; Russell, Scott; Patel, Rupal
Abstract: Purpose: To explore the influence of listener profession on impressions of speakers with dysarthria with varying intelligibility using semantic differential scales. M ethod: Three listener groups (undergraduate students, emergency workers, speech–language pathologists (SLPs); n = 38) rated non-speech attributes of six adults with dysarthria that ranged from low to high speech intelligibility. Participants rated 22 bipolar adjective pairs and listening effort on visual analogue scales. Following factor analysis of the semantic differential scales, listener impression and effort ratings were compared across listening groups and speaker intelligibility. Result: Repeated measures ANOVA revealed that neither impressions nor effort ratings differed across listener groups. However, impressions significantly decreased and listening effort significantly increased with reduced intelligibility. Analysis of the semantic differential scale items revealed two factors (Capability, Personality) that predicted 52% of the variance. Listener impressions were significantly higher for Personality than Capability. C onclusion: Preliminary findings suggest that speakers with dysarthria with reduced intelligibility are at risk to be negatively judged, particularly on their physical and mental capability. This study demonstrates the promise of employing semantic differential scales to investigate listener impressions and therefore the daily communication experiences of speakers with dysarthria. SLPs should consider patient experience of negative impressions when designing treatment.